A new invariant of lattice polytopes - Bruns, Winfried; Hibi, Takayuki (MATHEMATICA SCANDINAVICA, 2024)
The maximal degree of monomials belonging to the unique minimal system of monomial generators of the canonical module ω (K[P]) of the toric ring K[P] defined by a lattice polytope P will be studied. It is shown that if P possesses an interior lattice point, then the maximal degree is at most P - 1, and that this bound is the best possible in general.